Anticipate : - Thomas, Bill (John Wiley & Sons, 2013)
This book provides business readers with a practical how-to approach for taking their customer-supplier relationship to one that is more sustainable and more mutually profitable. Much of the discussion on customer experience has centered on the hospitality or retail industries and has showcased the discrete techniques organizations use to deliver better service and create more satisfied customers. Anticipate extends and integrates those techniques to deliver an end-to-end customer experience that can be applied in any industry, by any type of organization. Get proven guidance on how to design and implement a customer-focused journey that moves beyond the transaction and satisfied customers, to a relationship and culture that creates and leverages loyalty -- and the profitability that comes with it.